Investigation into folate metabolism and the effects of Methotrexate on folate metabolism in relation to the MTHFR C677T mutation in cultured mammalian cells - McCarthy, Fiona (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2005)
An English physician in 1920 identified an anaemia seen frequently in late pregnancy which responded well to treatment with a yeast extract called marmite (Wills, 1931). She called this anaemia "pernicious anaemia of late pregnancy" because of its similarities with pernicious anaemia, the difference being that this anaemia disappeared once the pregnancy ended. Mitchell later identified the active ingredient in the yeast as being folic acid/folate (Mitchell et ai, 1988). In 1941 Mitchell et al, were the first to isolate and purify folic acid from spinach leaves (Mitchell et al., 1988).
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin